Pengaruh Live Streaming, Online customer Review, Cashback Promotion Dan Discount Flash sale Terhadap Minat Beli Brand Pinkflash Di Aplikasi Shopee - Aini, Syarifa; Rizal, Mohammad; Mahardani, Ahmad Subhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The development of digital technology has driven the growth of e-commerce in Indonesia, with Shopee as one of the leading platforms. One of the cosmetic Brands that has expanded through e-commerce is PinkFlash. This research seeks to examine the impact the influence of Live Streaming, online customer reviews, cashback promotions, and flash sales discounts on consumer purchasing decisions purchase intention for the  PinkFlash Brand on the Shopee application. This research employs a quantitative method with an explanatory research approach. The sample consists of students from Universitas Islam Malang who have purchased PinkFlash products on Shopee, with a total of 90 respondents. The sampling technique used is proportional sampling, and data is collected through questionnaires analyzed using multiple linear regression analysis. The results indicate that, simultaneously, Live Streaming, online customer Reviews, cashback promotions, and discount flash sales significantly influence purchase intention. Partially, the features of Live Streaming and online customer reviews have a noteworthy and positive impact on purchase intention, while cashback promotions and discount flash sales also contribute to increasing consumer attraction to PinkFlash products. These findings highlight the crucial role of digital marketing strategies in shaping consumer purchasing decisions in e-commerce. Keywords: Purchase Intention, Live Broadcast, Online Customer Feedback, Cashback Offers, Flash Discounts,  Shopee, PinkFlash.